Prevalence of diabetes among stroke patients: a study in a tertiary care centre - Mallikarjuna Rao, Kande V.; Reddy, G. Pavan Kumar (International Journal of Advances in Medicine, 2017)
Background: Stroke is an abrupt onset of neurological deficit that is attributed to a vascular cause. Diabetes mellitus is known to be one of the major risk factors for stroke, apart from hypertension, ischemic heart disease, alcoholism, smoking, family history and hyperlipidemia. Since it was found that the serum glucose levels were elevated immediately after stroke, we had conducted this study to identify the clinical profile of the patients who suffered stroke, especially in relation to their glycemic status. Methods: Detailed demographic, physical and clinical history was taken from the patients and their relatives. Within 3 days of the onset of symptoms related to stroke, CT scan was performed on all patients to confirm diagnosis and to categorize the type and size of stroke. Based on the glucose levels, the patients were divided into euglycemic, known diabetic, newly detected diabetes and stress hyperglycemia. Results: The most common age in which stroke occurred was 50-60 years (55%), followed by 61-70 years (27.1%). 31.8% of the patients were known diabetic and the least was stress hyperglycemic with 8.5%. 51(39.5%) of the patients had ischemic stroke while 78 (60.5%) had hemorrhagic stroke. Conclusions: Diabetes is a very important risk factor associated with high morbidity and mortality.